Polish(ed) : Poland rooted in Canadian fiction - Nowaczyk, Małgorzata; Jaronczyk, Kasia (2017)
"What is the literary and cultural benefit of a diaspora anthology? It presents work from a community, a family of writers. It represents a cultural contribution to Canadian literature. It makes it known where they come from personally and metaphorically, what inspires them. In thir case, they are all writers who share Polish-ness, in whatever ways we define it, as a part of their personal story, be it through similar experiences, influences, and perspective on the world, a sense of history and of who they are. And also, through interest in Polish diaspora, writers who have no Polish roots.